The Moral Identity Of Youth Who Do Not Smoke: Internalization Predicts Their Preference Towards Smoking And Non-smoking Behaviour - Muaz Haqim Shaharum; Nasir Yusoff; Azwa Abdul Aziz; Kuay Hue San; Sabarisah Hashim; Roslee Ahmad (Malaysian Journal of Public Health Medicine, 2024)
Indexed by Scopus/MyCite